Studies of fresh water foam fungi of Uttara Kannada, Karnataka - and S. VIJAYKUMAR, CH. RAMESH (Indian Phytopathology, 2005)
Foam formed in aquatic ecosystems acts as a trap for many fungal spores and in particular of aquatic Hyphomycetes. Therefore foam samples collected were scanned for a period of two years. This survey revealed the presence of 36 species of foam flora out of which 8 species are new to Karnataka and 9 species are new additions to the fungi of India. However spores of Beltrania, Curvularia and Tetraploa were also observed. All the fungi observed have been discussed in the paper.